Tidal Dissipation and Eccentricity Pumping: Implications for the Depth of the Secondary Eclipse of 55 Cnc e. Issue Volume 8:Issue S299(2013) (6th January 2014) - Bolmont, E.; Selsis, F.; Raymond, S. N.; Leconte, J.; Hersant, F.; Maurin, A.-S.; Pericaud, J.
Abstract: We use the super-Earth 55 Cnc e (Fischer et al . 2008) as a case-study to address an observable effect of tidal heating. This transiting short-period planet belongs to a compact multiple system with massive planets. We investigate whether planet-planet interactions can force the eccentricity of this planet to a level that would affect the eclipse depth observed with Spitzer.